Having the backup when the heat is on. - McHardy, Anne (Times Higher Education Supplement, 2001)
Reports on the high- and low-tech procedures used to save vital programs when a fire ravaged the informatics department at City University in London, England. Backup system; Storage of sensitive data on tapes that are on separate sites.